The secret identity of Devon Delaney - Barnholdt, Lauren (New York : Aladdin Mix, 2007)
While spending the summer with her grandmother, Devon met Lexi, whom she lied to by saying she was popular and had a boyfriend; now her new friend attends her school and Devon must try to cover up her untruths.
5.0
5-8
5-8
School Library Journal
Booklist
Kliatt
Keywords: Honesty -- Fiction; High school students -- Fiction; Dating (Social customs) -- Fiction; Grandmothers -- Fiction; Schools -- Fiction; Honesty -- Fiction; High school students -- Fiction; Dating (Social customs) -- Fiction; Grandmothers -- Fiction; School stories